Greenland peregrines at their eyries - a behavioral study of the peregrine falcon - Harris, James T.; Clement, David M. (Meddelelser om Grønland, 1975)
Two families of the endangered peregrine falcon (Falco peregrinus tundrius) were observed at their nest cliffs in West Greenland. This article describes the breeding behavior of the tundra peregrine, including vocalizations, prey species, feeding and hunting, activity cycles, parental roles, and inter- and intraspecific behavior.